2004
DOI: 10.1016/j.ehj.2004.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Short-term benefit of smoking cessation in patients with coronary heart disease: estimates based on self-reported smoking data and serum cotinine measurements

Abstract: The benefits of non-smoking and smoking cessation in cardiac patients are beyond controversy and might even be larger than suggested by previous studies which exclusively relied on self-reported smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
0
23
1
2
Order By: Relevance
“…Some small studies indicate that benefits from smoking cessation may occur as early as 1 year after acute coronary syndrome presentation, but they do not have enough data to evaluate whether such short-term benefits are observed in apparently healthy people [22]. In our study we demonstrated that smoking cessation improves clot properties, which may provide an additional reason for smokers to cease smoking.…”
Section: Discussionmentioning
confidence: 44%
“…Some small studies indicate that benefits from smoking cessation may occur as early as 1 year after acute coronary syndrome presentation, but they do not have enough data to evaluate whether such short-term benefits are observed in apparently healthy people [22]. In our study we demonstrated that smoking cessation improves clot properties, which may provide an additional reason for smokers to cease smoking.…”
Section: Discussionmentioning
confidence: 44%
“…However, some degree of measurement error may still be present and would thus result in residual confounding (Skuladottir et al, 2004). We suggest that better modelling and use of biomarkers (such as cotinine) should be used in future studies, to better assess smoke exposure (Twardella et al, 2004). Second, consumers of F&V may quit smoking more often or more rapidly than non-consumers.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data reinforce the findings of previous research. Current studies show that smoking cessation in patients with CVD reduced the rate of recurrent CVD events by 40%, after 1-year follow-up, 12 and the mortality rate due to recurrent CVD events by 17%, after 20-year follow-up. 13 In the United States, pioneering studies 14 -18 have examined smoking cessation in patients who were already diagnosed with CVD.…”
mentioning
confidence: 94%